An ultrathin gradient aerogel composite structure for power battery thermal runaway suppression and a preparation method thereof
Patent Information
- Application Number
- CN202611102500.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-11-03
AI Technical Summary
Existing aerogel insulation structures cannot actively control the direction of heat flow. When the thickness is less than 3mm, it is difficult to balance thermal insulation performance, flame retardant performance and mechanical strength. The interlayer bonding force is insufficient, and it is easy to delaminate at high temperatures. It has poor high-temperature stability and cannot meet the long-term protection requirements for thermal runaway of power batteries.
An ultra-thin gradient aerogel composite structure is adopted, consisting of a fiber-reinforced aerogel layer, a gradient flame-retardant layer, a directional thermal conduction layer, and a high-temperature resistant protective layer stacked sequentially from the inside out. The gradient flame-retardant layer automatically expands at high temperatures to form a carbonized heat insulation layer. Combined with the low thermal conductivity of the fiber-reinforced aerogel layer and the directional thermal conduction of the directional thermal conduction layer, active control of heat flow direction and passive thermal protection are achieved.
Active control of heat flow direction under ultra-thin conditions significantly prolongs the thermal runaway propagation delay time, improves mechanical strength and high-temperature stability, and ensures the safety and protection effect of power batteries.
Smart Images

Figure CN123025540A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of thermal safety protection technology for power batteries and energy storage systems of new energy vehicles, specifically relating to an ultrathin gradient aerogel composite structure and its preparation method for suppressing thermal runaway of power batteries. Background Technology
[0002] With the rapid development of new energy vehicles and large-scale energy storage systems, the energy density of power batteries is constantly increasing, and the risk of thermal runaway is significantly increasing. When thermal runaway occurs, the local temperature of a power battery can rise rapidly to over 600°C, and through heat conduction, heat radiation and flame propagation, it can trigger a chain failure of adjacent cells, causing serious safety accidents.
[0003] Currently, commonly used thermal insulation materials for power batteries include ceramic fiber thermal insulation pads, mica boards, flame-retardant foam, and aerogel composite materials. Among them, aerogel materials are widely used in the field of power battery thermal insulation due to their ultra-low thermal conductivity (usually less than 0.025 W / (m·K)).
[0004] However, existing technologies still have the following problems:
[0005] 1. The direction of heat flow cannot be actively controlled: Most existing aerogel insulation structures adopt a uniform heat conduction system, which only has static heat insulation function and cannot achieve active control of the direction of heat flow. This results in heat spreading evenly in all directions during thermal runaway, and cannot effectively block the lateral transfer of heat to adjacent cells.
[0006] 2. Difficulty in achieving comprehensive performance under ultra-thin conditions: When the overall structural thickness is less than 3mm, traditional aerogel structures cannot simultaneously balance thermal insulation performance, flame retardant performance and mechanical strength, often sacrificing one aspect of performance to meet thickness requirements.
[0007] 3. Insufficient interlayer bonding, prone to delamination at high temperatures: Existing structures are usually prepared by simple lamination or coating, resulting in insufficient interlayer bonding. Under high-temperature thermal shock, interlayer delamination is prone to occur, which cannot effectively suppress the lateral diffusion of thermal runaway.
[0008] 4. Poor high-temperature stability: The aerogel matrix is prone to pulverization under high temperature conditions, and the flame retardant components are prone to failure under continuous high temperature, resulting in a sharp decline in overall protection performance, which cannot meet the long-term protection requirements under the thermal runaway conditions of power batteries.
[0009] To this end, we propose an ultrathin gradient aerogel composite structure and its preparation method for suppressing thermal runaway in power batteries. Summary of the Invention
[0010] The purpose of this invention is to provide an ultrathin gradient aerogel composite structure and its preparation method for suppressing thermal runaway in power batteries, so as to solve the problems mentioned in the background art.
[0011] To achieve the above objectives, the present invention provides the following technical solution: an ultrathin gradient aerogel composite structure for suppressing thermal runaway in power batteries, comprising layers stacked sequentially from the inside out:
[0012] A fiber-reinforced aerogel layer, serving as the main insulation layer, has a thickness of 0.8-1.5 mm.
[0013] A gradient flame-retardant layer containing intumescent flame-retardant components and ceramic flame-retardant components, with a thickness of 0.2-0.8 mm;
[0014] A directional heat-conducting layer is placed in the area corresponding to the local heat source, with a thickness of 0.05-0.3mm;
[0015] A high-temperature resistant protective layer, serving as the outermost layer, has a thickness of 0.05-0.5mm;
[0016] The overall thickness of the composite structure is less than or equal to 3 mm, forming a gradient thermal management aerogel composite structure with lateral thermal insulation, longitudinal thermal conduction, and high-temperature expansion flame retardancy.
[0017] Preferably, the thermal conductivity of the fiber-reinforced aerogel layer is less than or equal to 0.020 W / (m·K);
[0018] The fiber-reinforced aerogel layer is prepared by impregnating a fiber felt with silica aerogel and then drying it. The fiber felt can be any one of glass fiber felt, ceramic fiber felt, or aramid fiber felt.
[0019] Preferably, the gradient flame retardant layer comprises the following components by weight percentage:
[0020] Intumescent flame retardant component 30-50 wt%;
[0021] Ceramicized flame retardant component 20-40 wt%;
[0022] High-temperature charring components: 10-30 wt%;
[0023] Adhesive 5-15wt%.
[0024] Preferably, the intumescent flame retardant component is at least one of ammonium polyphosphate or melamine polyphosphate;
[0025] The ceramicized flame-retardant component is at least one of aluminum silicate, zinc borate, or low-melting-point glass powder;
[0026] The high-temperature charring component is at least one of pentaerythritol, dipentaerythritol, or expandable graphite.
[0027] Preferably, the gradient flame retardant layer forms a component gradient distribution along the thickness direction, with the mass percentage of the intumescent flame retardant component on the side closer to the fiber-reinforced aerogel layer being higher than that on the side farther from the fiber-reinforced aerogel layer, and the mass percentage of the ceramicized flame retardant component on the side farther from the fiber-reinforced aerogel layer being higher than that on the side closer to the fiber-reinforced aerogel layer.
[0028] Preferably, the thermal conductivity of the directional heat-conducting layer along the longitudinal direction is greater than 5 W / (m·K);
[0029] The directional heat-conducting layer is any one of graphite heat-conducting sheet, boron nitride heat-conducting film, or metallized heat-conducting mesh.
[0030] Preferably, the high-temperature resistant protective layer has a temperature resistance of 400℃ or higher;
[0031] The high-temperature resistant protective layer is any one of polyimide film, ceramic-coated polyester film, or silicon-oxygen composite film.
[0032] A method for preparing an ultrathin gradient aerogel composite structure for suppressing thermal runaway in power batteries includes the following steps:
[0033] S1. The fiber felt is impregnated in silica aerogel sol, and after gel aging, solvent replacement, surface modification and drying, a fiber-reinforced aerogel layer is obtained.
[0034] S2. Apply the flame retardant component slurry to the surface of the fiber-reinforced aerogel layer in 2 to 4 coats to form a gradient flame retardant layer. After each coat, pre-cur at 60-100℃ for 10-30 min.
[0035] S3. Embed thermally conductive material in a preset area to form a directional thermally conductive layer;
[0036] S4. The high-temperature resistant protective layer is laminated onto the outer surface of the structure using a hot-pressing composite method. The hot-pressing temperature is 80-180℃ and the hot-pressing pressure is 0.2-1MPa.
[0037] S5. Post-process the composite structure to obtain an ultrathin gradient aerogel composite structure with an overall thickness of less than or equal to 3 mm.
[0038] Preferably, the drying in step S1 is supercritical drying, with the following drying conditions: liquid CO2 as the medium, temperature 35-50℃, pressure 8-15MPa, and drying time 4-12h.
[0039] Preferably, the post-treatment in step S5 includes: curing at 60-120°C for 1-4 hours and performing stress relief treatment.
[0040] Compared with the prior art, the beneficial effects of the present invention are:
[0041] 1. Gradient thermal management to achieve active control of heat flow direction: This invention provides low lateral thermal conductivity (thermal conductivity ≤0.020W / (m·K)) through a fiber-reinforced aerogel layer, achieves longitudinal directional thermal conduction through a directional thermal conduction layer (thermal conductivity ≥5W / (m·K)) through a gradient flame-retardant layer, and achieves high-temperature expansion flame retardancy through a gradient flame-retardant layer. The three work together to form a complete gradient thermal management system, which achieves active control of heat flow direction and effectively blocks the lateral diffusion of heat to adjacent cells.
[0042] 2. Ultra-thin and efficient, meeting space-constrained requirements: Under the condition of an overall thickness of less than or equal to 3mm, this invention maintains excellent heat insulation performance, flame retardant performance and mechanical strength through the synergistic cooperation of each functional layer, fully meeting the application requirements of power batteries with limited space.
[0043] 3. Adaptive flame retardancy and passive thermal protection: The gradient flame retardant layer automatically expands to form a carbonized heat insulation layer under thermal runaway high temperature conditions, realizing passive adaptive thermal protection without the need for external triggering conditions, and the response is rapid and reliable.
[0044] 4. Significantly extends the thermal runaway propagation delay time: This invention can significantly extend the thermal runaway propagation delay time to greater than or equal to 10 minutes, buying valuable time for personnel evacuation and emergency response. Test results of the embodiments show that the thermal runaway propagation delay time can reach 10.8-14.1 minutes, which is 136% higher than that of the non-gradient flame retardant layer.
[0045] 5. Excellent high-temperature structural stability: The present invention maintains structural integrity under 800℃ thermal shock conditions, with no obvious delamination or powdering. The gradient distribution design of the gradient flame retardant layer effectively avoids interlayer separation caused by thermal stress mismatch at high temperatures, and the high-temperature resistant protective layer further enhances the overall structure's resistance to powdering. Attached Figure Description
[0046] Figure 1 This is a schematic cross-sectional view of the ultrathin gradient aerogel composite structure of the present invention;
[0047] Figure 2 This is a schematic diagram illustrating the principle of directional heat flow conduction in this invention;
[0048] Figure 3 This is a schematic diagram of the high-temperature expansion flame-retardant state of the present invention;
[0049] Figure 4 This is a schematic diagram of the gradient distribution of the components in the gradient flame retardant layer of the present invention;
[0050] Figure 5 The thermal runaway test temperature-time curves of Embodiment 1 and Comparative Example 1 of the present invention are shown. Detailed Implementation
[0051] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0052] Please see Figures 1-4 The ultrathin gradient aerogel composite structure for suppressing thermal runaway in power batteries provided by this invention comprises, from the inside out: a fiber-reinforced aerogel layer, a gradient flame-retardant layer, a directional thermally conductive layer, and a high-temperature resistant protective layer.
[0053] The fiber-reinforced aerogel layer serves as the main thermal insulation layer, with a thickness of 0.8-1.5 mm. The thermal conductivity of the fiber-reinforced aerogel layer is less than or equal to 0.020 W / (m·K), exhibiting low lateral thermal conductivity, which is used to block the lateral diffusion of heat between adjacent cells.
[0054] The fiber-reinforced aerogel layer is prepared by impregnating silica aerogel with fiber felt and then drying it. The fiber felt can be any one of glass fiber felt, ceramic fiber felt or aramid fiber felt. The introduction of the fiber skeleton effectively solves the problem of high brittleness and easy pulverization of pure aerogel, and improves the mechanical strength and vibration resistance of the composite structure.
[0055] A gradient flame-retardant layer is disposed on the surface of the fiber-reinforced aerogel layer, with a thickness of 0.2-0.8 mm. The gradient flame-retardant layer contains the following components by mass percentage:
[0056] Intumescent flame retardant component: 30-50 wt%;
[0057] Ceramicized flame retardant component: 20-40 wt%;
[0058] High-temperature charring components: 10-30 wt%;
[0059] Adhesive: 5-15wt%.
[0060] The intumescent flame retardant component is at least one of ammonium polyphosphate or melamine polyphosphate; the ceramicized flame retardant component is at least one of aluminum silicate, zinc borate or low melting point glass powder; the high-temperature charring component is at least one of pentaerythritol, dipentaerythritol or expandable graphite.
[0061] The gradient flame retardant layer forms a component gradient distribution along the thickness direction: the mass percentage of the intumescent flame retardant component on the side closer to the fiber-reinforced aerogel layer is higher than that on the side farther from the fiber-reinforced aerogel layer, and the mass percentage of the ceramic flame retardant component on the side farther from the fiber-reinforced aerogel layer is higher than that on the side closer to the fiber-reinforced aerogel layer.
[0062] That is, the inner side is mainly composed of intumescent flame retardant components, which rapidly expand at high temperatures to form a porous carbonized heat insulation layer; the outer side is mainly composed of ceramic flame retardant components, which form a dense ceramicized protective layer at high temperatures to improve barrier performance. The gradient flame retardant layer undergoes micro-expansion under high temperature conditions to form a porous carbonized heat insulation layer, with an expansion ratio of 2 to 5 times.
[0063] A directional heat-conducting layer is disposed in the area corresponding to the local heat source of the composite structure, with a thickness of 0.05-0.3mm. The thermal conductivity of the directional heat-conducting layer along the longitudinal direction is greater than or equal to 5W / (m·K). It is used to conduct the heat of the local hot spot to the heat dissipation surface along the longitudinal direction, reducing the risk of heat diffusion between adjacent cells. The directional heat-conducting layer can be any one of graphite thermal conductive sheet, boron nitride thermal conductive film or metallized thermal conductive mesh.
[0064] The high-temperature resistant protective layer, as the outermost layer, has a thickness of 0.05-0.5mm and a temperature resistance greater than or equal to 400℃. It is used to improve the overall mechanical strength of the structure, prevent aerogel powdering, and block external flames. The high-temperature resistant protective layer can be any one of polyimide film, ceramic-coated polyester film, or silicone composite film.
[0065] The overall thickness of the composite structure is less than or equal to 3 mm, forming a gradient thermal management aerogel composite structure with low thermal conductivity in the transverse direction, directional thermal conductivity in the longitudinal direction, and high-temperature expansion flame retardancy.
[0066] This invention also provides a method for preparing an ultrathin gradient aerogel composite structure, comprising the following steps:
[0067] S1. Preparation of fiber-reinforced aerogel layer: The fiber felt is impregnated in silica aerogel sol, and after gel aging, solvent replacement, surface modification and drying, the fiber-reinforced aerogel layer is obtained.
[0068] The gel aging temperature is 40-60℃ and the time is 12-24h. Solvent replacement is carried out with n-hexane 2-3 times. Surface modification is carried out with trimethylchlorosilane / n-hexane solution at a concentration of 5-10 vol%. Drying is supercritical drying under the following conditions: liquid CO2 as medium, temperature 35-50℃, pressure 8-15MPa, and drying time 4-12h.
[0069] S2. Forming a gradient flame retardant layer: The flame retardant component slurry is coated in 2-4 coats to form a gradient flame retardant layer on the surface of the fiber-reinforced aerogel layer. After each coating, it is pre-cured at 60-100℃ for 10-30 minutes. By controlling the component ratio of each coating, the gradient distribution of the flame retardant component along the thickness direction is achieved.
[0070] S3. Set up a directional heat conduction layer: embed heat conduction material in a preset area to form a directional heat conduction layer. Specifically, embed graphite heat conduction sheet, boron nitride heat conduction film or metallized heat conduction mesh in the preset area and fix it with a heat-sensitive adhesive to form a longitudinal directional heat conduction channel.
[0071] S4. Composite high-temperature resistant protective layer: The high-temperature resistant protective layer is composited onto the outer surface of the structure by hot pressing. The hot pressing temperature is 80-180℃, the hot pressing pressure is 0.2-1.MPa, and the holding time is 5-15min.
[0072] S5. Post-treatment: The composite structure is post-treated, including curing at 60-120℃ for 1-4 hours and stress release treatment, to obtain an ultrathin gradient aerogel composite structure with an overall thickness of less than or equal to 3 mm.
[0073] The present invention will be further described in detail below with reference to specific embodiments:
[0074] Example 1:
[0075] An ultrathin gradient aerogel composite structure for suppressing thermal runaway in power batteries, comprising, from the inside out:
[0076] Fiber-reinforced aerogel layer: 1.2 mm thick, made by impregnating glass fiber mat with silica aerogel and supercritical drying, with a thermal conductivity of 0.017 W / (m·K);
[0077] Gradient flame retardant layer: 0.5 mm thick, containing the following components by mass percentage: 40 wt% ammonium polyphosphate, 25 wt% aluminum silicate, 20 wt% pentaerythritol, and 15 wt% binder, distributed in a gradient along the thickness direction (rich in ammonium polyphosphate on the inside and rich in aluminum silicate on the outside).
[0078] Directional heat conduction layer: 0.1mm thick, made of graphite heat conduction sheet, with a longitudinal thermal conductivity of 8W / (m·K);
[0079] High-temperature resistant protective layer: 0.2mm thick, made of polyimide film, temperature resistant to 500℃;
[0080] The overall thickness is 2.0mm.
[0081] The preparation method of this embodiment includes the following steps:
[0082] S1. Glass fiber mat is impregnated in silica aerogel sol and gel aged at 50°C for 18 hours. The solvent is replaced three times with n-hexane. The surface is modified with a trimethylchlorosilane / n-hexane solution with a concentration of 8 vol%. Then, the fiber-reinforced aerogel layer is obtained by supercritical drying at 45°C and 12 MPa using liquid CO2 as the medium.
[0083] S2. The flame retardant component slurry is applied in three coats to form a gradient flame retardant layer on the surface of the fiber-reinforced aerogel layer. After each coat, it is pre-cured at 80°C for 20 minutes. By controlling the component ratio of each coat, the content of ammonium polyphosphate on the side closer to the fiber-reinforced aerogel layer is higher than that on the side farther away, and the content of aluminum silicate on the side farther away from the fiber-reinforced aerogel layer is higher than that on the side closer to the fiber-reinforced aerogel layer.
[0084] S3. Embed a graphite heat-conducting sheet in the preset area and fix it with a heat-sensitive adhesive to form a directional heat-conducting layer;
[0085] S4. The polyimide film is laminated onto the outer surface of the structure by hot pressing. The hot pressing temperature is 130℃, the hot pressing pressure is 0.6MPa, and the holding time is 10min.
[0086] S5. Curing at 90℃ for 2.5h and performing stress release treatment to obtain an ultrathin gradient aerogel composite structure with an overall thickness of 2.0mm.
[0087] Performance test results:
[0088] Transverse thermal conductivity: 0.017 W / (m·K);
[0089] Longitudinal thermal conductivity: 8.2 W / (m·K);
[0090] Thermal runaway propagation delay time: 12.3 min (refer to GB38031-2020 test method);
[0091] Flame penetration time: >15 min;
[0092] Structural integrity after 800℃ thermal shock: no delamination, no pulverization.
[0093] Example 2:
[0094] An ultrathin gradient aerogel composite structure for suppressing thermal runaway in power batteries, comprising, from the inside out:
[0095] Fiber-reinforced aerogel layer: 1.0 mm thick, made by impregnating ceramic fiber felt with silica aerogel and supercritical drying, with a thermal conductivity of 0.019 W / (m·K);
[0096] Gradient flame retardant layer: 0.6 mm thick, containing the following components by mass percentage: 35 wt% melamine polyphosphate, 30 wt% zinc borate, 20 wt% dipentaerythritol, and 15 wt% binder, distributed in a gradient along the thickness direction;
[0097] Directional heat conduction layer: 0.15mm thick, made of boron nitride thermal conductive film, with a longitudinal thermal conductivity of 6W / (m·K);
[0098] High-temperature protective layer: 0.25mm thick, made of ceramic-coated polyester film, with a temperature resistance of 450℃;
[0099] The overall thickness is 2.0mm.
[0100] The preparation method steps in this embodiment are basically the same as those in Example 1, except that: in step S1, the gel aging temperature is 40℃ and the time is 24h, the supercritical drying temperature is 35℃, the pressure is 8MPa and the time is 12h; in step S2, the coating is applied 4 times, and the pre-curing temperature is 60℃ and the time is 30min each time; in step S4, the hot pressing temperature is 80℃, the pressure is 1.0MPa and the holding time is 15min; in step S5, the curing temperature is 60℃ and the time is 4h.
[0101] Performance test results:
[0102] Transverse thermal conductivity: 0.019 W / (m·K);
[0103] Longitudinal thermal conductivity: 6.5 W / (m·K);
[0104] Thermal runaway propagation delay time: 10.8 min;
[0105] Flame penetration time: >12 min;
[0106] Structural integrity after 800℃ thermal shock: no delamination, no pulverization.
[0107] Example 3:
[0108] An ultrathin gradient aerogel composite structure for suppressing thermal runaway in power batteries, comprising, from the inside out:
[0109] Fiber-reinforced aerogel layer: 1.5 mm thick, made by impregnating aramid fiber felt with silica aerogel and supercritical drying, with a thermal conductivity of 0.016 W / (m·K);
[0110] Gradient flame retardant layer: 0.4 mm thick, containing the following components by mass percentage: 30 wt% ammonium polyphosphate, 25 wt% low melting point glass powder, 25 wt% expandable graphite, and 20 wt% binder, distributed in a gradient along the thickness direction;
[0111] Directional heat conduction layer: 0.2mm thick, using metallized heat conduction mesh, with a longitudinal thermal conductivity of 10W / (m·K);
[0112] High-temperature resistant protective layer: 0.3mm thick, made of silicon-oxygen composite film, temperature resistant up to 420℃;
[0113] The overall thickness is 2.4mm.
[0114] The preparation method steps in this embodiment are basically the same as those in Example 1, except that: in step S1, the gel aging temperature is 60℃ and the time is 12h, the supercritical drying temperature is 50℃, the pressure is 15MPa and the time is 4h; in step S2, the coating is applied twice, and the pre-curing temperature is 100℃ and the time is 10min each time; in step S4, the hot pressing temperature is 180℃, the pressure is 0.2MPa and the holding time is 5min; in step S5, the curing temperature is 120℃ and the time is 1h.
[0115] Performance test results:
[0116] Transverse thermal conductivity: 0.016 W / (m·K);
[0117] Longitudinal thermal conductivity: 10.5 W / (m·K);
[0118] Thermal runaway propagation delay time: 14.1 min;
[0119] Flame penetration time: >18 min;
[0120] Structural integrity after 800℃ thermal shock: no delamination, no pulverization.
[0121] Comparative Example 1:
[0122] The difference between Comparative Example 1 and Example 1 is that the gradient flame retardant layer is removed, and only the fiber-reinforced aerogel layer (1.2 mm thick), the directional heat conduction layer (0.1 mm thick), and the high-temperature resistant protective layer (0.2 mm thick) are retained, with an overall thickness of 1.5 mm. The remaining structure and parameters are the same as in Example 1.
[0123] Performance test results: The thermal runaway propagation delay time was only 5.2 minutes, the flame penetration time was 6 minutes, and local pulverization occurred after thermal shock at 800℃. This indicates that without a gradient flame retardant layer, the composite structure cannot form an effective carbonized heat insulation barrier at high temperatures, and heat quickly penetrates the structural layer, resulting in a sharp decline in thermal protection performance.
[0124] Comparative Example 2:
[0125] The difference between Comparative Example 2 and Example 1 is that the gradient flame retardant layer adopts a uniform mixing coating method (that is, ammonium polyphosphate, aluminum silicate, pentaerythritol and binder are uniformly mixed in the same proportion and coated in one time, without component gradient distribution along the thickness direction). The rest of the structure and parameters are the same as those in Example 1, and the total thickness of the gradient flame retardant layer is still 0.5 mm.
[0126] Performance test results: The thermal runaway propagation delay time was 8.5 min, the flame penetration time was 10 min, and slight interlaminar delamination occurred after thermal shock at 800℃, indicating that the component gradient distribution has a significant effect on improving thermal protection performance.
[0127] Rui Figure 5 As shown, compared with Comparative Example 1, Example 1 showed an improvement of approximately 136% in thermal runaway propagation delay time (from 5.2 min to 12.3 min) and approximately 150% in flame penetration time.
[0128] Compared to Comparative Example 2, Example 1 showed a 45% improvement in thermal runaway propagation delay time (from 8.5 min to 12.3 min), indicating significantly better high-temperature structural stability.
[0129] The above comparison shows that the present invention, through the gradient distribution design of the components of the gradient flame retardant layer, especially the gradient structure with the inner side rich in intumescent flame retardant components and the outer side rich in ceramic flame retardant components, can exert the synergistic effect of expansion into char for heat insulation and ceramic dense protection under high temperature conditions of thermal runaway, and significantly improve the thermal protection performance and high temperature structural stability.
[0130] The present invention has the following beneficial effects:
[0131] 1. Gradient thermal management to achieve active control of heat flow direction: This invention provides low lateral thermal conductivity (thermal conductivity ≤0.020W / (m·K)) through a fiber-reinforced aerogel layer, achieves longitudinal directional thermal conduction through a directional thermal conduction layer (thermal conductivity ≥5W / (m·K)) through a gradient flame-retardant layer, and achieves high-temperature expansion flame retardancy through a gradient flame-retardant layer. The three work together to form a complete gradient thermal management system, which achieves active control of heat flow direction and effectively blocks the lateral diffusion of heat to adjacent cells.
[0132] 2. Ultra-thin and efficient, meeting space-constrained requirements: Under the condition of an overall thickness of less than or equal to 3mm, this invention maintains excellent heat insulation performance, flame retardant performance and mechanical strength through the synergistic cooperation of each functional layer, fully meeting the application requirements of power batteries with limited space.
[0133] 3. Adaptive flame retardancy and passive thermal protection: The gradient flame retardant layer automatically expands to form a carbonized heat insulation layer under thermal runaway high temperature conditions, realizing passive adaptive thermal protection without the need for external triggering conditions, and the response is rapid and reliable.
[0134] 4. Significantly extends the thermal runaway propagation delay time: This invention can significantly extend the thermal runaway propagation delay time to greater than or equal to 10 minutes, buying valuable time for personnel evacuation and emergency response. Test results of the embodiments show that the thermal runaway propagation delay time can reach 10.8-14.1 minutes, which is 136% higher than that of the non-gradient flame retardant layer.
[0135] 5. Excellent high-temperature structural stability: The present invention maintains structural integrity under 800℃ thermal shock conditions, with no obvious delamination or powdering. The gradient distribution design of the gradient flame retardant layer effectively avoids interlayer separation caused by thermal stress mismatch at high temperatures, and the high-temperature resistant protective layer further enhances the overall structure's resistance to powdering.
[0136] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. An ultrathin gradient aerogel composite structure for suppressing thermal runaway in power batteries, characterized in that, Including those arranged in layers from the inside out: A fiber-reinforced aerogel layer, serving as the main insulation layer, has a thickness of 0.8-1.5 mm. A gradient flame-retardant layer containing intumescent flame-retardant components and ceramic flame-retardant components, with a thickness of 0.2-0.8 mm; A directional heat-conducting layer is placed in the area corresponding to the local heat source, with a thickness of 0.05-0.3mm; A high-temperature resistant protective layer, serving as the outermost layer, has a thickness of 0.05-0.5mm; The overall thickness of the composite structure is less than or equal to 3 mm, forming a gradient thermal management aerogel composite structure with lateral thermal insulation, longitudinal thermal conduction, and high-temperature expansion flame retardancy.
2. The ultrathin gradient aerogel composite structure for suppressing thermal runaway in power batteries according to claim 1, characterized in that: The thermal conductivity of the fiber-reinforced aerogel layer is less than or equal to 0.020 W / (m·K); The fiber-reinforced aerogel layer is prepared by impregnating a fiber felt with silica aerogel and then drying it. The fiber felt is any one of glass fiber felt, ceramic fiber felt, or aramid fiber felt.
3. The ultrathin gradient aerogel composite structure for suppressing thermal runaway in power batteries according to claim 1, characterized in that: The gradient flame-retardant layer comprises the following components by mass percentage: Intumescent flame retardant component 30-50 wt%; Ceramicized flame retardant component 20-40 wt%; High-temperature charring components: 10-30 wt%; Adhesive 5-15wt%.
4. The ultrathin gradient aerogel composite structure for suppressing thermal runaway in power batteries according to claim 3, characterized in that: The intumescent flame retardant component is at least one of ammonium polyphosphate or melamine polyphosphate; The ceramicized flame-retardant component is at least one of aluminum silicate, zinc borate, or low-melting-point glass powder. The high-temperature char-forming component is at least one of pentaerythritol, dipentaerythritol, or expandable graphite.
5. The ultrathin gradient aerogel composite structure for suppressing thermal runaway in power batteries according to claim 3, characterized in that: The gradient flame retardant layer forms a component gradient distribution along the thickness direction. The mass percentage of the intumescent flame retardant component on the side closer to the fiber-reinforced aerogel layer is higher than that on the side farther from the fiber-reinforced aerogel layer, and the mass percentage of the ceramicized flame retardant component on the side farther from the fiber-reinforced aerogel layer is higher than that on the side closer to the fiber-reinforced aerogel layer.
6. The ultrathin gradient aerogel composite structure for suppressing thermal runaway in power batteries according to claim 1, characterized in that: The thermal conductivity of the directional heat-conducting layer along the longitudinal direction is greater than 5 W / (m·K); The directional heat-conducting layer is any one of graphite heat-conducting sheet, boron nitride heat-conducting film, or metallized heat-conducting mesh.
7. The ultrathin gradient aerogel composite structure for suppressing thermal runaway in power batteries according to claim 1, characterized in that: The high-temperature resistant protective layer has a temperature resistance of 400℃ or higher; The high-temperature resistant protective layer is any one of polyimide film, ceramic-coated polyester film, or silicon-oxygen composite film.
8. A method for preparing an ultrathin gradient aerogel composite structure for suppressing thermal runaway in power batteries as described in any one of claims 1-7, characterized in that, Includes the following steps: S1. The fiber felt is impregnated in silica aerogel sol, and after gel aging, solvent replacement, surface modification and drying, a fiber-reinforced aerogel layer is obtained. S2. Apply the flame retardant component slurry to the surface of the fiber-reinforced aerogel layer in 2 to 4 coats to form a gradient flame retardant layer. After each coat, pre-cur at 60-100℃ for 10-30 min. S3. Embed thermally conductive material in a preset area to form a directional thermally conductive layer; S4. The high-temperature resistant protective layer is laminated onto the outer surface of the structure using a hot-pressing composite method. The hot-pressing temperature is 80-180℃ and the hot-pressing pressure is 0.2-1MPa. S5. Post-process the composite structure to obtain an ultrathin gradient aerogel composite structure with an overall thickness of less than or equal to 3 mm.
9. The method for preparing an ultrathin gradient aerogel composite structure for suppressing thermal runaway in power batteries according to claim 8, characterized in that: The drying described in step S1 is supercritical drying, and the drying conditions are: liquid CO2 as the medium, temperature 35-50℃, pressure 8-15MPa, and drying time 4-12h.
10. The method for preparing an ultrathin gradient aerogel composite structure for suppressing thermal runaway in power batteries according to claim 8, characterized in that: The post-treatment described in step S5 includes curing at 60-120℃ for 1-4 hours and performing stress relief treatment.
